2020
DOI: 10.1021/acs.chemrestox.0c00208
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Immunotoxicity of Polycaprolactone Nanoparticles—Effects of Polymer Molecular Weight, Hydrolysis, and Blends

Abstract: Poly-ε-caprolactone (PCL) is a biodegradable polyester that has FDA and CE approval as a medical device. Nonetheless, the lack of toxicity exhibited by the polymer cannot be extrapolated to its nanomaterial conformation. Despite PCL-based NPs being widely studied in the biomedical field for their advantages as controlled drug delivery systems, little data describe PCL NPs’ toxicity, particularly immunotoxicity. This work assessed different PCL-based delivery systems intended for protein delivery regarding thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…81,105 Few have investigated this polymer's broader bioactivity. 86,121,122 Recent work on another common biomedical polymer, polylactic acid (PLA), has shown that ingested PLA microplastics can shed nanoplastics and oligomers in the gut, leading to acute inflammation and the translocation of particles from the gut to other tissues. 123 Polyethylene wear particles have similarly been shown to migrate from orthopedic implants to lymphatic tissues and contribute to device failure via small particle disease.…”
Section: Biomedicalmentioning
confidence: 99%
“…81,105 Few have investigated this polymer's broader bioactivity. 86,121,122 Recent work on another common biomedical polymer, polylactic acid (PLA), has shown that ingested PLA microplastics can shed nanoplastics and oligomers in the gut, leading to acute inflammation and the translocation of particles from the gut to other tissues. 123 Polyethylene wear particles have similarly been shown to migrate from orthopedic implants to lymphatic tissues and contribute to device failure via small particle disease.…”
Section: Biomedicalmentioning
confidence: 99%
“…Studies which account for in vitro cell viability and in vivo effect and fate of polymersomes are generally carried out with polymers whose biodegradability and biocompatibility are wellestablished, such as poly(DL-lactide), poly(trimethylene carbonate), and poly(caprolactone). [61][62][63][64][65][66] More recent publications on polymersomes involving less-frequently studied polymers or polymers bearing additional functional species have little biodegradability and biocompatibility data available, hence requiring extensive work to establish their suitability for medicinal purposes. 5,[67][68][69][70] Fig.…”
Section: Biodegradable Polymersomesmentioning
confidence: 99%
“…PCL has great potential for use in the engineered myocardium. Given its widespread usage in other tissue engineering fields, PCL has a proven track record of integration with cells in vitro and organs in vivo . , Additionally, PCL has been granted FDA approval for use in implantable medical devices, setting a precedent for its use in implantable engineered tissues . Future research on PCL-based scaffolds should include the incorporation of the described principles of anisotropic reinforcement and ECM deposition, as well as the promotion of angiogenesis and immune modulation, improvement of mechanical properties and CM maturation on the scaffold, and in vivo investigation into the effects of mechanical degradation on tissue integration.…”
Section: Future Directions and Significance Of Pcl In Cardiac Enginee...mentioning
confidence: 99%
“…48,50 Additionally, PCL has been granted FDA approval for use in implantable medical devices, setting a precedent for its use in implantable engineered tissues. 180 Future research on PCLbased scaffolds should include the incorporation of the described principles of anisotropic reinforcement and ECM deposition, as well as the promotion of angiogenesis and immune modulation, improvement of mechanical properties and CM maturation on the scaffold, and in vivo investigation into the effects of mechanical degradation on tissue integration. On the basis of the research reviewed, much progress has been made toward a three-dimensional, anisotropic fibrous scaffold of biodegradable PCL and its integration with the ECM, angiogenic factors, electroactive materials, hydrogels, and cardiomyocytes.…”
Section: ■ Future Directions and Significance Of Pcl In Cardiac Engin...mentioning
confidence: 99%